2005
DOI: 10.1038/sj.bjc.6602643
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density and the risk of breast cancer in Japanese women

Abstract: Using an automated method for detecting mammographic mass, the authors evaluated the relation between quantitatively measured density and the risk of breast cancer in a case -control study among Japanese women. The case subjects were 146 women newly diagnosed and histologically confirmed with breast cancer at a general hospital. A total of 659 control women were selected from those who attended a breast cancer mass screening at this hospital. Significantly increased odds ratios (ORs) of breast cancer were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 25 publications
6
57
0
Order By: Relevance
“…Although the majority of studies were conducted in Caucasian populations, four were carried out in Asia, and their findings were consistent with the overall pooled effects (54,57,59,61). Four U.S. studies presented ethnic groupspecific associations (1,29,31,42).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Although the majority of studies were conducted in Caucasian populations, four were carried out in Asia, and their findings were consistent with the overall pooled effects (54,57,59,61). Four U.S. studies presented ethnic groupspecific associations (1,29,31,42).…”
Section: Resultssupporting
confidence: 51%
“…2, 3, 10, 27, 29, 30, 32-44), whereas prevalence studies were case-control or crosssectional (Table 2; refs. 1,28,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Nine studies were conducted using symptomatic populations or controls (Table 3; refs.…”
Section: Resultsmentioning
confidence: 99%
“…Whether the discrepancy between the two studies is due to unmeasured differences between the Asian populations in Los Angeles and Hawaii, or to other reasons is unknown. In a study of Japanese women (25), where mean breast size was considerably smaller than in the present study, the adjusted increases in risk per 1% mammographic density was 0.7% (P trend = 0.22) and 2.3% (P trend = 0.005) in premenopausal and postmenopausal, respectively. The corresponding value in our study as reported previously was 1.1% for African American, 1.5% for White, and 3.0% for Asian American women (3).…”
Section: Discussionmentioning
confidence: 93%
“…A high percentage of dense area has been associated with an f3-to 6-fold increased risk of breast cancer in most of the studies, which adopted quantitative assessment methods (1). We have developed an automated method for detecting mammographic density (2) and confirmed a positive association between breast density and breast cancer risk among Japanese women (3).…”
Section: Introductionmentioning
confidence: 85%